2013
DOI: 10.1002/jcc.23347
|View full text |Cite
|
Sign up to set email alerts
|

The ORP basis set designed for optical rotation calculations

Abstract: Details of generation of the optical rotation prediction (ORP) basis set developed for accurate optical rotation (OR) calculations are presented. Specific rotation calculations carried out at the density functional theory (DFT) level for model chiral methane molecule, fluorooxirane, methyloxirane, and dimethylmethylenecyclopropane reveal that the ORP set outperforms larger basis sets, among them the aug-cc-pVTZ basis set of Dunning (J. Chem. Phys. 1989, 90, 1007) and the aug-pc-2 basis set of Jensen (J. Chem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 66 publications
2
61
1
Order By: Relevance
“…As mentioned earlier, the LPol‐ n family recommended for electric property evaluation suffers from strong near‐linear dependence, which leads to removal of a substantial number of functions even in the case of relatively small systems. Contrary, our earlier DFT/B3LYP study revealed that the near‐linear dependence for the ORP basis set is similar to that for other medium‐size basis sets, which means that the use of ORP set in the calculations carried out for larger molecular systems is not likely to lead to numerical problems . In the present work the near‐linear dependence of the R‐ORP basis set functions has been investigated.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…As mentioned earlier, the LPol‐ n family recommended for electric property evaluation suffers from strong near‐linear dependence, which leads to removal of a substantial number of functions even in the case of relatively small systems. Contrary, our earlier DFT/B3LYP study revealed that the near‐linear dependence for the ORP basis set is similar to that for other medium‐size basis sets, which means that the use of ORP set in the calculations carried out for larger molecular systems is not likely to lead to numerical problems . In the present work the near‐linear dependence of the R‐ORP basis set functions has been investigated.…”
Section: Resultsmentioning
confidence: 67%
“…It stems from the method of generation of the LPol‐ n sets, resulting in polarization functions having the same exponents as those already present in the source basis set . The LPol‐ n sets are known to suffer from the near‐linear dependence even in the case of relatively small molecules, and the number of functions removed from the total set soon becomes substantial . The removal of the basis functions decreases the size of the basis set in a not fully controlled manner, which in turn may affect the accuracy of investigated system description.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been only quite recently that the optical rotation prediction (ORP) basis set has been developed by some of the present authors for investigation of specific rotation of organic molecules. 17 The ORP basis set is derived from the VTZ basis set of Ahlrichs et al 18 augmented with one diffuse s-type and one diffuse p-type functions. The ORP basis set has the size very close to the LPol-ds basis set, however it was found to be more resistant to the occurence of linear dependencies in the molecular basis set.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to fill this gap, in the present work we investigate electric properties (electronic and vibrational) using the property-oriented Pol and LPol-ds basis sets of Sadlej and co-workers, 10,38 the def2-SVPD and def2-TZVPD sets of Rappoport and Furche, 15 and the ORP basis set reported recently by Baranowska-Łączkowska and Łączkowski. 17 Additionally, we use the aug-cc-pVXZ and d-aug-cc-pVXZ (X=D,T,Q) basis sets of Dunning and co-workers. [1][2][3] We combine these basis sets with the second-order Møller and Plesset perturbation theory (MP2) approach and CCSD(T) method to evaluate the diagonal components of the static electronic dipole polarizability, first and second hyperpolarizabilities.…”
Section: Introductionmentioning
confidence: 99%